2021
DOI: 10.1111/fwb.13697
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressure influence activity and assembly of bacterial communities in reservoir sediments

Abstract: Reservoir sediments are subjected to highly variable hydrostatic pressures, but little is known about the direct impacts of this environmental variable on microbial communities and biogeochemical processes mediated by microbes in the numerous deep reservoirs (>100 m) scattered across our planet. To address this gap, the organic matter degradation and community assembly of sediment bacteria were studied in bioreactors maintained under different hydrostatic pressures (0.5–3.0 MPa) and explored using 16S rRNA amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…ANOSIM (analysis of similarity) further demonstrated that there were significant differences in microbial communities at different pressures ( Table S5 ). These findings are consistent with findings from previous pressure incubation experiments with surface seawaters [ 36 ], sediments [ 64 ], and sinking POM [ 20 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…ANOSIM (analysis of similarity) further demonstrated that there were significant differences in microbial communities at different pressures ( Table S5 ). These findings are consistent with findings from previous pressure incubation experiments with surface seawaters [ 36 ], sediments [ 64 ], and sinking POM [ 20 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest a significant decrease in microbial diversity under HHP and LT conditions ( Figure 1 ). One possible explanation is that the metabolic activity and cellular processes of microbial communities seem to be inhibited by HHP and LT; therefore, a large number of microbial cells may die or tend to be dormant under unfavorable environments [ 30 , 32 , 64 , 65 ]. Similar variation trends were observed in microbial communities of pressure-induced sediment samples [ 64 ] and during sinking particles degradation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation